ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGOBATAN MALARIA DI KABUPATEN SAROLANGUN PROVINSI JAMBI TAHUN 2015 - Amir Farouk (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
In the case of malaria Sarolangun ranks 10th AMI and API Comparison of the total population and the incidence of malaria cases is highest in Singkut health center with a total number of 481 patients with AMI 21.20%, and API 242 (3.38%). Unknown factors related to malaria treatment compliance so that the formulation of the problem is what are the factors related to malaria treatment compliance in Sarolangun. The purpose of this study was to analyze factors associated with compliance of malaria treatment in Sarolangun Jambi Province.This research is an explanatory research with cross sectional design. Samples are patients who tested positive for malaria through laboratory tests. The number of samples in this research were 122 respondents. The results showed 60.7% of respondents have less compliance in the treatment of malaria compared with good adherence of 30.9%. Statistical analysis of variables that were statistically show that the dominant influence is the knowledge about malaria with 0,024 value ρ (ρ <0.05) with POR / Exp (B) 3376 and 95% CI = 1175-9701; perceptions of barriers where ρ value <0.001 (ρ <0.05) with POR / Exp (B) 8352 and CI 95% = 2925-23847; support families with ρ value 0,003 (ρ <0.05) with POR / Exp (B) 7113 and CI 95% = 1926-26272. Other factors that are not related to malaria treatment compliance were age, education, income, long suffering from malaria and perception of vulnerability (ρ> 0.05)Statistically significant variables as risk factors for malaria treatment compliance is knowledge about malaria, perception of barriers, as well as family support.Keywords : Perception, compliance of treatment, Malaria